1999
DOI: 10.1111/j.1469-7793.1999.0539p.x
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+ permeability and kinetics of glutamate receptors in rat medial habenula neurones: implications for purinergic transmission in this nucleus

Abstract: We have previously investigated P2X receptor‐mediated synaptic currents in medial habenula neurones and shown that they can be calcium permeable. We now investigate the receptor properties of glutamate, the other, more abundant excitatory transmitter, to determine its receptor subtypes and their relative calcium permeability. This may have implications for the physiological role of the P2X receptors which mediate synaptic currents. Using fast application of ATP, L‐glutamate or kainate to nucleated patches, glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 44 publications
0
25
0
Order By: Relevance
“…3A). Minimal or no differences occurred in the thalamic nuclei or habenula, suggestive of low NMDA receptor activity (21). Post hoc analyses showed that cell death increased significantly in the F group, with no differences between the C, KF, and K groups.…”
Section: Repetitive Inflammatory Painmentioning
confidence: 93%
“…3A). Minimal or no differences occurred in the thalamic nuclei or habenula, suggestive of low NMDA receptor activity (21). Post hoc analyses showed that cell death increased significantly in the F group, with no differences between the C, KF, and K groups.…”
Section: Repetitive Inflammatory Painmentioning
confidence: 93%
“…In addition to nAChRs, MHb neurons express P2X receptors, which, upon ATP release from the TS, cause a substantial Ca 2+ influx into the neuron (Edwards et al, 1992; Edwards et al, 1997; Robertson et al, 1999; Rogers et al, 1997). Ca 2+ is an important intracellular messenger, modulating ion channels and altering synaptic function, and α4β2* and α3β4* nAChRs show a fairly high Ca 2+ -permeability (Ragozzino et al, 1998; Rathouz and Berg, 1994).…”
Section: Electrophysiological Properties Of the Mhb-ipn Circuitrymentioning
confidence: 99%
“…Ca 2+ is an important intracellular messenger, modulating ion channels and altering synaptic function, and α4β2* and α3β4* nAChRs show a fairly high Ca 2+ -permeability (Ragozzino et al, 1998; Rathouz and Berg, 1994). Together, P2X and nAChRs, likely make up for the lack of Ca 2+ current mediated by NMDARs, which are not expressed in the MHb (Robertson et al, 1999; Rogers and Dani, 1995). Functionally, ATP has been shown to both depolarize and increase spontaneous AP activity in hypocretin/orexin neurons (Wollmann et al, 2005).…”
Section: Electrophysiological Properties Of the Mhb-ipn Circuitrymentioning
confidence: 99%
“…Nevertheless, numerous types of ion channels show appreciable permeability to Ca 2+ (summarized in Table 1), so imaging of SCCaFTs has widespread potential applicability. The various families of voltage-gated Ca 2+ channels are the most obvious mechanisms for regulating plasma membrane Ca 2+ flux, but growing evidence emphasizes also the importance of numerous ligand-gated channels [39][40][41][42][43][44][45], among which attention has focused on nicotinic acetylcholine receptors (nAChRs) and ionotropic glutamate receptors (GluR) because of their involvement in synaptic transmission.…”
Section: Perspective and Future Applicability Of Single-channel Ca 2+mentioning
confidence: 99%